Role of the Aspergillus-Specific IgG and IgM Test in the Diagnosis and Follow-Up of Chronic Pulmonary Aspergillosis - Li, Hongxing; Rui, Yuwen; Zhou, Wei; Liu, Lulu; He, Binchan; Shi, Yi; Su, Xin (Frontiers in Microbiology, 2019)
Background Chronic pulmonary aspergillosis (CPA) has a high rate of misdiagnosis and has been reported to have an increasing rate of morbidity and mortality. In this article, we assessed the serum Aspergillus-specific IgG and IgM test in the diagnosis of patients with CPA. Methods A prospective study was conducted from January 2016 to July 2017 in Nanjing Jinling Hospital. Serum samples were collected from CPA patients (178 sera, 82 patients) and from non-aspergillosis patients (125 sera) with community-acquired pneumonia (CAP), active tuberculosis, bronchiectasis or lung tumors. Additionally, we included a control group of healthy patients(50 sera). Aspergillus-specific antibody detection was performed using a Dynamiker ELISA kit, and the results were compared with the value of galactomannan (GM) in bronchoalveolar lavage fluid (BALF). Results The sensitivity and specificity of the Aspergillus-specific IgG antibody in the diagnosis of CPA were 84.1 and 89.6%, respectively. These values were slightly higher compared to those obtained for the sensitivity and specificity using the BALF GM test (79.1 and 84.2%, respectively). However, the sensitivity and specificity of Aspergillus-specific IgM antibody were only 43.9 and 87.2%, respectively. Moreover, the positive rate of IgG in patients with subacute invasive aspergillosis (SAIA) was 87%, compared to the positive rates of IgG in CPA patients sick for 3–6 months (80.0%), 6–9 months (81.8%) and ≥9 months (80.0%). Meanwhile, the positive rate of IgM in SAIA patients was 63%, compared to the positive rate of IgM in CPA patients sick for 3–6 months (46.7%), 6–9 months (0%) and ≥9 months (0%), respectively. Furthermore, serum IgG levels decreased gradually in the majority of CPA patients who showed positive response to antifungal therapy, and IgG levels increased in two CPA patients when their disease worsened. Conclusion A serum Aspergillus-specific IgG test is a valuable tool for the diagnosis of CPA and SAIA, while an Aspergillus-specific IgM test is only modestly specific for the diagnosis of SAIA. Overall, the variation trend of Aspergillus-specific IgG levels may reflect the therapeutic effectiveness in the long-term follow-up of CPA.